Effects of coupled sulphate and temperature on internal strain and strength evolution of cemented paste backfill at early age. (10th January 2020) - Yan, Baoxu; Zhu, Wancheng; Hou, Chen; Yu, Yongjun; Guan, Kai
Highlights: Internal strain of sulphated CPB that related to strength development can be considered as a hydration process indicator. Sulpahte concentration and curing temperature can significantly affect the evolution of internal strain in CPB. Final internal strain is an important indicator for the barricades stability as well as mining cycle. Abstract: Cement hydration is a volume reduction reaction which can result in negative pore water pressure while strengthening the structural stiffness of cemented paste backfill (CPB). Both sulphate and temperature significantly affect the hydration process and thus influence the internal volume change and mechanical properties of CPB. The expansive hydration products produced in sulphated CPB may create an increase in volume which subsequently weakens the CPB. This paper presents an experimental study conducted to evaluate the coupled effects of sulphate and curing temperature on the internal strain evolution of early aged CPB. CPB samples of various initial sulphate concentrations (0, 5000 and 25, 000 ppm) were prepared and cured at various temperature (20 °C and 35 °C) at early ages (≤7 days). Mechanical tests were conducted on the samples as internal strain was monitored by Fiber Bragg Grating (FBG) sensors. The results indicate that the FBG sensor is sufficiently sensitive to detect the internal strain development of sulphated CPB mixtures during the hydration process. At sulphate concentration of 25, 000 ppm, the expansive strain occurred at curing temperature of 35 °C due to the internal expansive force of the expansive materials. The final internal strain value corresponds closely to the strength of the sulphated CPB. As the internal strain of sulphated CPB decreased, the uniaxial compressive strength and tensile strength showed similar trends throughout the experiment. When expansive strain emerged after the initial thermal strain stage, however, there was a higher ratio of uniaxial compressive strength to tensile strength. This phenomenon merits careful consideration in the stability analysis of exposed CPB in underground mines.